(3GdJUQja Gdedhcis - (3YKeGf Hf Lfj GdehUdj, CHh GdaJM, GHf Lfj,J (B392 (3g` s
(3ChdgG (B:s
(3bGd CHh GdaJM YKeGf Hf Lfi QMeg Gddg JYGdi (B: (3gPg Led ef CUhd GdJUQja jbQH JCedgG , hJbd GdcdaI Yf edJeS GdaGFOI efgG s
(3BNQgG (B:s
(3hCeG GdEOZGe adg bSe HQCSg hGddg CYde Je GdeNJUQ Gdedhci HMeO Gddg hYhfg hMSf Jhajbg hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi fHjg eMeO hBdg Bejf s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B204 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B652s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI LGeYI Gdedc YHO GdYRjR GdeQcRjI HLOI s
Keywords: (3GdUQas